Crohn’s Disease Ocular Manifestations - Koev Kr. (Sciendo, 2014)
Crohn’s disease is an inflammatory bowel disease which causes inflammation of the digestive tract. Crohn’s disease most frequently affects the ileum and the colon. In the active stage of the disease signs and symptoms may include diarrhea, abdominal pain and cramping, blood in the stools, reduced appetite and weight loss. In patients with severe Crohn’s disease the following signs and symptoms may be observed: fever, fatigue, arthritis, eye inflammation, oral ulcers, skin disorders, inflammation of the liver or bile ducts or delayed growth. Heredity and dysfunctions of the immune system are considered to cause the development of Crohn’s disease. About 10% of people with inflammatory bowel disease have also ocular problems. The most common ocular manifestations of Crohn’s disease are uveitis, iritis, episcleritis, keratopathy, keratoconjunctivitis and retinal vasculitis. Untreated uveitis may cause glaucoma and vision loss. Uveitis and iritis are four times more common in women than in men. In patients in the active stage of the disease, episcleritis also flares. Symptoms of episcleritis include inflammation, bright red spots on the sclera and localized pain. Keratoconjunctivitis in Crohn’s disease is caused by decreased tear production or increased tear film evaporation. Dry eyes can cause itching, burning or infection. Keratopathy usually causes no pain or vision loss, therefore in most cases no treatment is needed. In retinal vasculitis tortuosity of retinal veins, retinal edema at the posterior pole and intraretinal blood near blood vessels are observed. Intravenous fluorescein angiography shows intraretinal neovascularisation and haemorrhage in the posterior pole.